The philosophy of nature : a guide to the new essentialism - Ellis, B. D. (Brian David), 1929- (McGill-Queen's University Press, 2002)
For many years essentialism was considered beyond the pale in philosophy, a relic of discredited Aristotelianism. This is no longer so. Kripke and Putnam have made belief in essential natures respectable once more. Harré and Madden have argued against Hume's theory of causation and developed an alternative theory based on the assumption that there are genuine causal powers in nature. Dretske, Tooley, Armstrong, Swoyer, and Carroll have all developed strong alternatives to Hume's theory of the laws of nature. And Shoemaker has developed a thoroughly non-Humean theory of properties. The "new essentialism" has evolved from these beginnings and can now reasonably claim to be a metaphysic for a modern scientific understanding of the world - one that challenges the conception of the world as comprising passive entities whose interactions are to be explained by appeal to contingent laws of nature externally imposed.